Internalizing and externalizing symptoms and suicidal behaviour in young people: a systematic review and meta‐analysis of longitudinal studies. (24th May 2019) - Soto‐Sanz, V.; Castellví, P.; Piqueras, J. A.; Rodríguez‐Marín, J.; Rodríguez‐Jiménez, T.; Miranda‐Mendizábal, A.; Parés‐Badell, O.; Almenara, J.; Alonso, I.; Blasco, M. J.; Cebrià, A.; Gabilondo, A.; et al.
Abstract : Objective: To assess internalizing and externalizing symptoms as risk factors for suicidal behaviour and suicide among adolescents and young adults. Method: We conducted a systematic review of articles published until January 2017. We identified 26 883 potential papers; 1701 full‐text articles were assessed for eligibility, of which 1479 were excluded because of methodological reasons. Diverse meta‐analyses were performed for each group of symptoms. Odds ratios (ORs) and 95% confidence intervals (95% CI) or beta coefficients for categorical variables, and effect size (ES) were calculated for continuous variables. Results: Finally, 41 studies were included, involving participants aged 12–26 years for a systematic review, and 24 articles were included for meta‐analysis. The meta‐analysis showed that youths with any internalizing (ES = 0.93) or externalizing symptoms (ES = 0.76 and OR = 2.59) were more likely to attempt suicide in future. This effect was also seen in depression symptoms (OR = 6.58 and ES = 1.00), legal problems (OR = 3.36), and anxiety (ES = 0.65). Conclusion: Reported internalizing and externalizing symptoms are predictors of suicide behaviour in young people; therefore, the detection and management of these symptoms in young populations could be a crucial strategy for preventing suicidality in this group.